Thermodynamic and column studies of Au(I) adsorption on weak alkaline anion exchange fibre from cyanide leaching solution. Issue 7 (2nd May 2016) - Li, Mingyu; Zheng, Juan; Zeng, Qingxuan; Shang, Xiaoqian
ABSTRACT: A novel method of adsorption of Au(I) from cyanide leaching solution with weak alkaline anion exchange fibre (WAAEF) was studied here. The thermodynamics of Au(I) from cyanide leaching solution by the WAAEF from 288 K to 308K have been investigated. Langmuir, Freundlich and Temkin models were adopted and the results confirmed that the Freundlich model fitted best with the equilibrium data. Thermodynamic calculation indicated that the absorption of Au(I) from cyanide leaching solution by WAAEF was an endothermic process with increased entropy. In the dynamic adsorption process, the optimal operational conditions, i.e . flow rate 670.0 BV⋅h −1, loading density 0.211 g⋅cm −3 and pH value 8.89 of the original solution, were obtained. Dynamic analytical analysis depicted that the elution yield could exceed up to 97% using a mixture of 3% H2 SO4 and 8% (NH2 )2 CS solution at a flow rate of 100.5 BV⋅h −1 .